Μαθηματικοί αλγόριθμοι για ανάλυση πιστοποιητικών ενεργειακής απόδοσης κτιρίων - Λαζαρής, Κυριάκος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This project began to thorough analysis of energy performance certificates of buildings and exporting various useful data on the energy consumption of buildings, as well as the implementation of a mathematical model which predicts various parameters with an 70% accuracy. Specifically at this project have been analysed 300 certificates of hotels in London, England. Furthermore, was made a simplification, process and an association with various parameters as shown below. The methodology used for the analysis of our data was made with the use of Excel and Tableau 8.3 programmes. The aim of this study is to highlight the energy class hotel in one of the busiest cities in the world with a large number of tourists yearly. Also, a second objective of this study is to show the importance and significance of 'Green Tourism' and whether the public is aware of that term. Finally, as the ultimate goal of the research is to construct a model which aims to inform the public about their stay at green hotels and come in touch with the term Green-Sustainable Tourism.
Keywords: Energy performance certificates of buildings; Energy consumption; Hotels; Green tourism; Πιστοποιητικά ενεργειακής απόδοσης κτιρίων (EPCs); Ενεργειακή κατανάλωση; Ξενοδοχεία; Πράσινος τουρισμός